The recording engineer´s handbook - Owsinski, Bobby (Course Technology Cengage Learning, 2009)
Working as a recording engineer presents challenges from every direction of your project. From using microphones to deciding on EQ settings, choosing outboard gear to understanding how, when and why to process your signal, the seemingly never-ending choices can be very confusing. Professional Audio''s bestselling author Bobby Owsinski (The Mixing Engineer''s Handbook, The Mastering Engineer''s Handbook) takes you into the tracking process for all manner of instruments and vocals-- providing you with the knowledge and skill to make sense of the many choices you have in any given project. From acoustic to electronic instruments, mic placement to EQ settings, everything you need to know to capture professionally recorded audio tracks is in this guide.